2012
DOI: 10.1007/s00415-012-6734-9
|View full text |Cite
|
Sign up to set email alerts
|

Global functional connectivity reveals highly significant differences between the vegetative and the minimally conscious state

Abstract: A major challenge in the diagnosis of disorders of consciousness is the differential diagnosis between the vegetative state (VS) and the minimally conscious state (MCS). Clinically, VS is defined by complete unawareness, whereas MCS is defined by the presence of inconsistent but clearly discernible behavioural signs of consciousness. In healthy individuals, pain cries have been reported to elicit functional activation within the pain matrix of the brain, which may be interpreted as empathic reaction. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 36 publications
7
36
0
1
Order By: Relevance
“…ACC and insula) in 30% of patients in a VS/UWS in response to noxious stimulation as well as pain cries [27,28] (Figure 1). The last study, nevertheless, also showed, in parallel to previous findings, that the connectivity within the whole pain network was significantly decreased as compared to patients in a MCS [29]. Even though this suggests an altered perception in patients in a VS/UWS, the activation of the affective pain network might denote the presence of residual pain perception Figure 1.…”
Section: Pain Processing and Disorders Of Consciousnesssupporting
confidence: 82%
“…ACC and insula) in 30% of patients in a VS/UWS in response to noxious stimulation as well as pain cries [27,28] (Figure 1). The last study, nevertheless, also showed, in parallel to previous findings, that the connectivity within the whole pain network was significantly decreased as compared to patients in a MCS [29]. Even though this suggests an altered perception in patients in a VS/UWS, the activation of the affective pain network might denote the presence of residual pain perception Figure 1.…”
Section: Pain Processing and Disorders Of Consciousnesssupporting
confidence: 82%
“…They showed extended functional networks in both MCS and healthy subjects, whereas no such functional connections were observed in VS. These results demonstrate the potential of functional connectivity MRI as a clinical tool for differential diagnosis in disorders of consciousness (Kotchoubey et al 2013). …”
Section: Clinical Relevance Of Rs-fmri In Doc Patientsmentioning
confidence: 91%
“…This finding lends further support to the notion that isolated cognitive processes may be preserved in VS, but that deficient connectivity is at the heart of decreased consciousness. Kotchoubey et al (2013) studied global functional connectivity under emotional load in 6 VS and 6 MCS patients who listened to recorded human pain cries compared to non-emotional vocalizations. While they observed no significant stimulusrelated activation in either group in a typical GLM analysis, a whole brain functional connectivity analysis revealed stronger connectivity in the MCS than in VS patients, in emotion-related networks similar to those observed in healthy controls.…”
Section: Resting State Activity and Functional Connectivitymentioning
confidence: 99%